On the direct product of two weak uniquely completable partial latin squares - Adams, Peter; Khodkar, Abdollah (Utilitas Mathematica, 2001)
In this note we show by counter-example that the direct product of two weak uniquely completable partial latin squares is not necessarily a uniquely completable partial latin square. This counter-example rejects a conjecture by Gower (see [3]) on the direct product of two uniquely completable partial latin squares.